(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article examines the semantic classification of proverbs into thematic groups in the Russian and Uzbek languages. As a result of the study, it was established that the characterized moral qualities, relationships between people, position in society, life experience, attitude to work, behavior, appearance, etc.